E-commerce as Marketing Media for Ruminant Feed and UMKM Craft Products Poto Village, Sumbawa - Andri Putraedi; Imam Munandar; Koko Hermanto; Yuliadi Yuliadi; M. Julkarnain; Yunari. W; Juniardi Akhir Putra (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
This study aims to design, develop, and test an e-commerce prototype as a digital marketing medium for ruminant animal feed products and micro, small, and medium enterprise (MSME) crafts in Poto Village, Sumbawa Regency. Local business actors in this area generally face two main challenges: limited access to broader markets and the lack of optimal utilization of digital technology for product promotion and sales. The study employed a qualitative research method to address these issues with data collected through observation, interviews, questionnaires, and literature studies. The developed e-commerce platform was then tested to evaluate its effectiveness and usability. The results show that the platform contributes positively by expanding the marketing reach of local products, increasing their competitiveness, and simplifying the transaction process. In addition, users expressed favorable responses to the simple interface, the clarity of product display, and the integrated communication features that facilitate direct interaction between sellers and buyers. These findings highlight that implementing an e-commerce system tailored to local needs has significant potential to strengthen the rural economy, particularly through the digitalization of MSMEs and the livestock feed sector. Testing further confirms that all e-commerce features function properly, meet user requirements, and are very easy to operate, thus providing evidence of the system's practicality and sustainability for long-term community use.